Identifying Chloride Content For Corrosion Under Insulation By Analytical Technique - Mohd Zaid, Nurul Widad; Ismail, Azzura (Research Progress in Mechanical and Manufacturing Engineering, 2021)
Corrosion can be defined as the destruction or deterioration of materials due to the electrochemical reaction with the environment. The factors that affect corrosion attacks include temperature, oxygen, pH and chloride. It is possible to describe proportion of chloride dissolved in solution contribute to salinity value. The purpose of this analysis is to measure amount of chloride content in water ingress absorbed in the insulation material. The temperature used in this research is 27 oC and the salinity ranges from 1 %, 2 %, 3 %, 3.5 % and 4 %. Due to strong similarities between the salts and lack of motivation to distinguish between all of them, spectral differences of concentration between an aqueous solution of NaCl have received minimal attention in previous research. The results show that correlating spectral measurements and the concentration of NaCl in liquid water can be applied up to the saturation point of salts and that solution of these salts of uncertain concentrations can be differentiated. Spectral data were obtained for NaCl samples and their concentrations were measured with an average error of 0.9 %. From this analysis, it is concluded that the corrosion rate can be caused by environmental conditions such as salinity concentration.